The Many Faces of Cryoglobulinemic Nephropathy: A Clinico-Pathologic Study of 47 Cases with Emphasis on the Value of Electron Microscopy. (5th September 2014) - Ojemakinde, Kunle; Turbat-Herrera, Elba A.; Zeng, Xu; Gu, Xin; Herrera, Guillermo A.
Abstract: The clinical and pathologic manifestations of cryoglobulinemic nephropathy (CN) are heterogeneous. The role that electron microscopy plays in the diagnosis of CN has not been properly evaluated. The main objective of this study was to define the value of ultrastructural evaluation in the diagnosis of CN. Although most of the CN cases in this series exhibited glomerular pathology with a membranoproliferative pattern, a significant number of the cases showed less well-defined morphologic patterns on light microscopic examination (i.e. mesangial proliferation, hyaline thrombi in glomerular capillaries without significant cellular proliferation, exudative glomerulonephritis, etc). Immunofluorescence microscopy also revealed variable immunoglobulin and complement component patterns, some with "full-house" expression of immunoreactants. A subset of these CN cases was associated with light chain restriction. Thus, differential diagnosis can be a challenge as many other glomerulonephritis overlap in immunomorphologic characteristics. Because the immunomorphologic manifestations of CN are so varied, confirmation of a suspected diagnosis of CN or making a diagnosis in a less than a typical immunomorphologic setting required careful ultrastructural evaluation to find unequivocal diagnostic findings or at least supportive evidence in the form of detection of substructure in the electron dense glomerular deposits consistent with cryoglobulins. Even in cases where the light and immunofluorescence findings in suspicious clinical situations were quite consistent with CN, electron microscopy provided the final proof to substantiate the diagnosis in the great majority of the cases.